Federated health information architecture: Enabling healthcare providers and policymakers to use data for decision-making. Issue 2 (May 2018) - Kumar, Manish; Mostafa, Javed; Ramaswamy, Rohit
Health information systems (HIS) in India, as in most other developing countries, support public health management but fail to enable healthcare providers to use data for delivering quality services. Such a failure is surprising, given that the population healthcare data that the system collects are aggregated from patient records. An important reason for this failure is that the health information architecture (HIA) of the HIS is designed primarily to serve the information needs of policymakers and program managers. India has recognised the architectural gaps in its HIS and proposes to develop an integrated HIA. An enabling HIA that attempts to balance the autonomy of local systems with the requirements of a centralised monitoring agency could meet the diverse information needs of various stakeholders. Given the lack of in-country knowledge and experience in designing such an HIA, this case study was undertaken to analyse HIS in the Bihar state of India and to understand whether it would enable healthcare providers, program managers and policymakers to use data for decision-making. Based on a literature review and data collected from interviews with key informants, this article proposes a federated HIA, which has the potential to improve HIS efficiency; provide flexibility for local innovation; cater to the diverse information needs of healthcare providers, program managers and policymakers; and encourage data-based decision-making.